2006
DOI: 10.1111/j.1582-4934.2006.tb00304.x
|View full text |Cite
|
Sign up to set email alerts
|

Differential upregulation of Nox homologues of NADPH oxidase by tumor necrosis factor‐α in human aortic smooth muscle and embryonic kidney cells

Abstract: Oxidative stress induced by superoxide (O 2¯⋅ ) and other reactive oxygen species (ROS) has critical roles in the pathogenesis of cardiovascular disease [1]. Potential enzymatic sources of ROS in vasculature include the mitochondrial respiration chain, lipoxygenase and cyclooxygenase, xanthine oxidase, NADPH oxidase, nitric oxide (NO) synthase and cytochrome P450 enzymes. Although our understanding of the mechanisms for superoxide production in vascular cells is incomplete, increasing evidence suggests that N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
61
0
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(68 citation statements)
references
References 41 publications
5
61
0
2
Order By: Relevance
“…(8,39,45). Those signal pathways may be involved in a myogenic response of the blood vessel (38,49).…”
Section: Discussionmentioning
confidence: 99%
“…(8,39,45). Those signal pathways may be involved in a myogenic response of the blood vessel (38,49).…”
Section: Discussionmentioning
confidence: 99%
“…Hypertension of vascular origin is associated with increased vascular contractility and with hypertrophy and proliferation of vascular smooth muscle and other cells. Nox enzymes (particularly Nox1) and ROS are induced in vascular cells by growth stimuli [Angiotensin II, PDGF, lyso-phosphatidylcholine, thrombin [42,44,64], urokinase plasminogen activator [65], by PGF2α and ATF-1 [66]] and by inflammatory stimuli [e.g., TNFα and IL1β [67]]. Nox1 was also markedly overexpressed in transgenic hypertensive rats overexpressing the Ren2 gene [64] and in stroke-prone spontaneously hypertensive rats [68].…”
Section: Nox Enzymes and Vascular Hypertensionmentioning
confidence: 99%
“…Nox4 is unique among other Nox isoenzymes in that its activity is constitutive and may depend on a specific conformation of the dehydrogenase DH domain that should allow a spontaneous transfer of electrons from NADPH to FAD and to the hemes [24,25]. Data from various studies indicated clearly that Nox4 activity is regulated at the mRNA level, implying that an increase or decrease of ROS production by Nox4 is correlated to an up regulation [9,16,[26][27][28][29][30][31][32][33] or to a decline [34] of Nox4 transcripts. Although it has not been reported yet, post-translational regulation of Nox4 oxidase activity cannot be excluded.…”
Section: Introductionmentioning
confidence: 99%